A Solution‐Processed Inorganic Emitter with High Spectral Selectivity for Efficient Subambient Radiative Cooling in Hot Humid Climates. Issue 12 (11th February 2022) - Lin, Chongjia; Li, Yang; Chi, Cheng; Kwon, Ye Seul; Huang, Jingyuan; Wu, Zuoxu; Zheng, Jiongzhi; Liu, Gongze; Tso, Chi Yan; Chao, Christopher Y. H.; Huang, Baoling
Abstract: Daytime radiative cooling provides an eco‐friendly solution to space cooling with zero energy consumption. Despite significant advances, most state‐of‐the‐art radiative coolers show broadband infrared emission with low spectral selectivity, which limits their cooling temperatures, especially in hot humid regions. Here, an all‐inorganic narrowband emitter comprising a solution‐derived SiO x N y layer sandwiched between a reflective substrate and a self‐assembly monolayer of SiO2 microspheres is reported. It shows a high and diffusive solar reflectance (96.4%) and strong infrared‐selective emittance (94.6%) with superior spectral selectivity (1.46). Remarkable subambient cooling of up to 5 °C in autumn and 2.5 °C in summer are achieved under high humidity without any solar shading or convection cover at noontime in a subtropical coastal city, Hong Kong. Owing to the all‐inorganic hydrophobic structure, the emitter shows outstanding resistance to ultraviolet and water in long‐term durability tests. The scalable‐solution‐based fabrication renders this stable high‐performance emitter promising for large‐scale deployment in various climates. Abstract : Different emissive behaviors between a bulk film and particles in reststrahlen band are utilized and an emitter with excellent spectrum selectivity is achieved. This emitter successfully realizes good subambient cooling in hot and humid conditions, which is always a challenge for radiative cooling. The all‐inorganic components and solution‐based fabrication process render it durable and scalable simultaneously.